2022
DOI: 10.1002/ped4.12328
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small vessel disease caused by PLOD3 mutation: Expanding the phenotypic spectrum of lysyl hydroxylase‐3 deficiency

Abstract: Introduction: Pathogenic variants in PLOD3, encoding lysyl hydroxylase-3 (LH3), can cause a hereditary connective tissue disorder that has rarely been reported. It is a multi-system disease, presenting with craniofacial dysmorphisms, skeletal and eye manifestations, sensorineural hearing loss, and variable skin manifestations. Severe central nervous system involvement has not been reported. Case presentation: A 10-month-old girl was admitted with development delay and clustered epileptic spasms. Hypertelorism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Consistent with this finding, Plod3 deficiency in the mouse caused basement membrane defects ( 44 , 45 ), suggesting that PLOD3 pathogenic variants may also contribute to intracerebral hemorrhages (ICHs), which constitute a central pathophysiological hallmark of Gould syndrome caused by COL4A1 and COL4A2 pathogenic variants ( 13 , 14 , 15 , 67 , 68 , 69 , 70 , 71 ). In addition, cerebrovascular hemorrhages have been reported in three patients with a connective tissue disorder caused by biallelic pathogenic variants of PLOD3 ( 39 , 43 ). To investigate the potential involvement of PLOD3 in ICH, we specifically evaluated the presence of PLOD3 variants in exome sequencing data from a fetal ICH cohort consisting of 113 probands who did not have COL4A1 or COL4A2 pathogenic variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this finding, Plod3 deficiency in the mouse caused basement membrane defects ( 44 , 45 ), suggesting that PLOD3 pathogenic variants may also contribute to intracerebral hemorrhages (ICHs), which constitute a central pathophysiological hallmark of Gould syndrome caused by COL4A1 and COL4A2 pathogenic variants ( 13 , 14 , 15 , 67 , 68 , 69 , 70 , 71 ). In addition, cerebrovascular hemorrhages have been reported in three patients with a connective tissue disorder caused by biallelic pathogenic variants of PLOD3 ( 39 , 43 ). To investigate the potential involvement of PLOD3 in ICH, we specifically evaluated the presence of PLOD3 variants in exome sequencing data from a fetal ICH cohort consisting of 113 probands who did not have COL4A1 or COL4A2 pathogenic variants.…”
Section: Resultsmentioning
confidence: 99%
“…DNA analysis showed biallelic PLOD3 variants (p.N223S/p.C691AfsX9) located in a conserved region of the LH3 amino acid sequence responsible for collagen glycosyltransferase and LH activities. Recently, a homozygous PLOD3 small inframe deletion was shown to cause a cerebral small vessel disease characterized by multiple white matter hypersignals and bleeding foci in an infant with a few dysmorphic features ( 43 ). To evaluate the contribution of PLOD3 pathogenic variants to cerebrovascular manifestations, we analyzed a series of 113 cases of fetal ICH that were negative for COL4A1 and COL4A2 pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no direct evidence of PLOD3 in AD has been reported, it is known to play an essential role in the formation of collagen, a major component of the ECM 84 . For instance, defects in PLOD3 (or Lysyl hydroxylase 3; LH3) have been implicated in causing inherited connective tissue disorders and have been shown to cause cerebral small vessel injury 85,86 , maintenance of the structural integrity of cerebral blood vessels, regulating inflammatory processes 87 . This enzyme is also a promising biomarker in AD, since its expression has been reported to fluctuate in cell-free RNA expression using blood samples from AD patients 88 .…”
Section: Discussionmentioning
confidence: 99%
“…The PLOD3 gene was further characterized the clinical features, which included joint contractures, low bone mineral density and fractures, scoliosis, myopia, sensorineural deafness, dysmorphic features, skin and nail abnormalities, and rupture of a vascular aneurysm (Ewans et al, 2019;Vahidnezhad et al, 2019). A recent study showed a homozygous mutation of c.1216_1218delCTC (p.L406del) in PLOD3, which was inherited from heterozygous parents (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%